Analysis of risk factors for subjective stress among nurses caring for patients with delirium: a cross-sectional, multicentre survey - Tianxiang Jiang; Yangling Ge; Wei Zhang; Xiaoqiong Wang; Weili Zhao; Xiaotong Yuan; Haochong He; Xiuzhi Zhang (BMC Nursing)
Abstract Background Nurses experience subjective stress and challenges in the context of caring for patients with delirium. These stresses can cause psychological damage to nurses and may affect the quality of delirium care. However, few multicentre studies have empirically explored the risk factors for subjective stress among nurses caring for patients with delirium. This study aimed to investigate the status of and risk factors for subjective stress among nurses caring for patients with delirium. Methods A multicentre, cross-sectional survey was conducted between November and December 2023 among a population-based convenience sample of nurses from three tertiary hospitals in Taizhou, Zhejiang Province. Demographic data, delirium care-related information, and scores on the Strain of Care for Delirium Index (SCDI) were collected for analysis. Results Hyperactive/hyperalert behavior had the highest overall mean score (3.18 ± 0.57), and hypoactive behavior had the lowest overall mean score (2.05 ± 0.58). The significant variables from the univariate analysis were included in multiple linear regression analysis for further analysis, with the SCDI total score as the dependent variable. Receiving training regarding delirium, having an intermediate title or above, working in a department with a standardized delirium management process, lower workload and more positive attitudes towards delirium were associated with lower levels of subjective stress among nurses caring for patients with delirium, accounting for 83.5% of the total variance. Conclusions This study provides insights into the risk factors for subjective stress among nurses caring for patients with delirium. Our findings suggest that educational programs, supportive measures, and standardized delirium management programs are crucial ways of reducing the burden faced by nurses. Nursing managers need to focus on the stresses experienced by nurses in the context of delirium care, address relevant barriers, and allocate appropriate resources. Clinical trial number Not applicable.